Smart Security System and Services / Zulfiqar Zailani ... [et.al.]. - Zailani, Zulfiqar; Sabparie, Muhammad Hafeez; Yahaya, Mohd Zulkarnain; Mohd Mortadza, Mohd Lutfi (2012)
In order to run a business more efficient and effective, there are certain criteria andconditions that are needed to be fulfilled. These require the involvement of effort and precision and distributing our services. These conditions will help in achieving our goals and will bring the business to be known. Firstly, the organisation must attain business or trade license from related authorities for the organisation's location in the market. In other words, the organisation must beregistered and recognised by the particular departments of government. Secondly, the demand and need of the clients must be recognised in order to satisfythe clients. This can be achieved by providing quality services that will gain interestto all parties and most importantly to the clients. When the requirement is fulfilled, the business can take step ahead to gain more profits and even gain more clients. Thirdly, all the equipment and machineries that the business has must be checkedand re-checked in order to avoid risk for the clients using it. The equipment andmachineries must be in good form and no damage. Clients' safety must be at the toppriority in our business because the risk comes mainly in our equipment and machineries provided. It is not only for the purpose of gaining clients to the business but also help in gaining their trust so that the numbers of clients will increase. It is their right according to law to enjoy the best quality services from the providers and must be treated of proper order.